1997
DOI: 10.1182/blood.v90.12.4979.4979_4979_4986
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Ferritin by Rat Hepatoma Cells and Its Regulation by Inflammatory Cytokines and Iron

Abstract: The possibility that serum ferritin is a secreted protein and an acute phase reactant regulated by inflammatory hormones and iron was examined in a hepatic cell line that secretes plasma proteins. Differentiated rat hepatoma cells released albumin and ferritin into the medium, as determined by rocket immunoelectrophoresis and isolation of ferritin by standard procedures plus immunoaffinity chromatography, following labeling with radioactive amino acid. Administration of interleukin-1–β (IL-1) or tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Although some differences were detected between the serum ferritin and the intracellular ferritin, the serum ferritin was shown to be tissue-derived through secretion. Under normal circumstances, equilibrium is maintained between intracellular and extracellular ferritin, but the concentration of ferritin in serum and other biological fluids may rise, depending on the iron status of the body, and under various physiological circumstances [17][18][19]. In a couple of studies, Ramm et al [20,21] showed that the administration of the microtubule depolymerizing drugs colchicine and vinblastine, in normal and iron-loaded rats, inhibited ferritin uptake and significantly increased the release of endogenous ferritin in both the serum and bile, suggesting that disturbed microtubule function could account for these results.…”
Section: Discussionmentioning
confidence: 99%
“…Although some differences were detected between the serum ferritin and the intracellular ferritin, the serum ferritin was shown to be tissue-derived through secretion. Under normal circumstances, equilibrium is maintained between intracellular and extracellular ferritin, but the concentration of ferritin in serum and other biological fluids may rise, depending on the iron status of the body, and under various physiological circumstances [17][18][19]. In a couple of studies, Ramm et al [20,21] showed that the administration of the microtubule depolymerizing drugs colchicine and vinblastine, in normal and iron-loaded rats, inhibited ferritin uptake and significantly increased the release of endogenous ferritin in both the serum and bile, suggesting that disturbed microtubule function could account for these results.…”
Section: Discussionmentioning
confidence: 99%
“…Two published studies have shown that serum ferritin is a protein secreted in response to exposure of cells to exogenous iron; it is distinct from intracellular ferritin. 27,28 Thus, this rise in serum ferritin can not be accounted for by release of ferritin from stores in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of ferritin can be increased in nonalcoholic fatty liver diseases, with higher levels in nonalcoholic steatohepatitis compared to simple steatosis (46,47). Increased ferritin could be independent of iron stores, and data suggest that it could be secondary to inflammation (47,48). Hence, reduction of ferritin levels in ob/+ mice treated with BAIBA could reflect lower necroinflammation ( Table 7).…”
Section: Articles Intervention and Preventionmentioning
confidence: 99%